Institutional Fragmentation and Urbanisation in the EU Cities - Federica Cappelli; Gianni Guastella; Stefano Pareglio (Fondazione Eni Enrico Mattei (FEEM), 2020)
This article examines the relationship between institutional fragmentation and the spatial extent of cities in Europe's Functional Urban Areas. European Union planning regulations vary across member states, but in most cases, local authorities determine land use within the more general regulatory frameworks set by national or subnational authorities. More decentralised and fragmented settings may favour urban sprawl, allowing developers to avoid land-use restrictions in one municipality by moving to adjacent ones and providing incentives for municipalities to adopt less strict land-conversion regulations to attract households and workers. The empirical results fully support this hypothesis and unveil significant differences between small and large cities, the effect of governance fragmentation being a substantial factor in the latter case.
Keywords: R52; R58; C24; 330; Urban Sprawl; Institutional Fragmentation; Threshold Regression